Chapter Il paesaggio di Leonardo. Fonti cartografiche e iconografiche - Leporatti, Silvia (Territori, 2023)
Leonardo's maps are to be analysed not only in relation to all his works, but also in the context of the cartography between the second half of the 15th century and the early 16th century and the techniques of so-called vedutismo pittorico. The aim of the contribution is to highlight - through a series of case studies - the potential of Leonardo's maps as sources for the reconstruction of the historical landscape. The research, starting from some of the maps produced by Leonardo, focused on two of the strands that appeared to be most significant: how to georeference Leonardo's maps in a GIS environment; topographical analysis aimed at recognising main population centres and road network.